Housing Construction: Stages of Development and Modern Trends - Zaiats, Ð¢etyana; Zaiats, Viacheslav (International Journal of Engineering and Technology, 2018)
The purpose of the study is to determine the specifics of housing construction at various stages of its evolutionary development in the context of the needs of the population in socially acceptable housing conditions. The methodological basis of the study is systematic, abstract-logical approaches and economic-statistical analysis. The main results are presented by the substantiation of the main stages of the development of housing construction, its technological and economic features in different socio-economic conditions, as well as the identification of trends in the development of this area in Ukraine, taking into account the housing needs of the population and the real possibilities of the economic system for their satisfaction. The emphasis is on maintaining the relevance of the housing problem in the country for a long time, the limited resource base on this and the uncertainty of the prospects for resolution due to the complex socio-political situation in the country and its regions. The global experience of financing housing construction is generalized, its elements are substantiated, acceptable for Ukraine. Recommendations for the further development of the sphere of housing construction, taking into account the achievements of the countries of the world, are described. Â Â